Successful transcatheter aortic valve implantation for severe aortic stenosis of a bicuspid valve with situs inversus totalis guided by advanced image processing: a case report. Issue 2 (4th May 2018) - Overtchouk, Pavel; Delhaye, Cédric; Sudre, Arnaud; Modine, Thomas
Abstract: Introduction: Transcatheter aortic valve implantation (TAVI) can be challenging in case of complex anatomy such as bicuspid aortic valve stenosis or situs inversus. This report illustrates a successful procedure in a patient with both conditions after careful pre-operative planning and per-operative guidance by means of a novel software. Case Presentation: We report the case of a 71-year-old man that presented a type 0 bicuspid aortic valve stenosis and situs inversus. We performed transfemoral TAVI using the Edwards Sapien 3 transcatheter heart valve (THV) and a novel software that provides insight for patient anatomy through computed tomography (CT) extracted three-dimensional reconstruction before the procedure aiming at improving THV positioning during the procedure through fusion of a CT-extracted virtual aortic annulus on the fluoroscopy screen and enhancing of calcifications that can be considered as anatomical landmarks. The Edwards Sapien 3 THV was accurately implanted in a supra-annular fashion. Post-operative echocardiography showed an excellent result without any para-prosthetic leak, and the patient reported symptom improvement. Discussion: During TAVI the angiographic appearance of the cusps of a bicuspid aortic valve is irregular and asymmetric, which can lead to malpositioning, paravalvular regurgitation, and increased rates of pacemaker implantation after TAVI. Furthermore, usual anatomical landmarks can be even more disturbed by the situs inversus totalis. We believe that pre-operative three-dimensional reconstruction and per-operative fluoroscopy image processing, provided by software such as the one presented in this case report, can provide precious guidance for TAVI in patients with complex and unusual anatomy.